Promoting health through personal change in social networks: A German–Danish partnership. (12th September 2019) - Wihofszky, Petra; Sternberg, Annika
The project Healthy in Everyday Life is a German–Danish partnership between local health promoters and researchers from the European University of Flensburg, Germany. The objective was to promote health opportunities at the local level by qualifying citizens as health mediators, who then become active in their neighbourhoods. It was implemented in the Danish municipalities of Sønderborg and Aabenraa and the German city of Flensburg. The project processes were evaluated using participatory research methods. The project partners worked together transnationally on all stages of the project, from the recruitment of participants, to training, the development of the evaluation design and the appraisal of evaluation results. The evaluation consisted of three levels: (1) health changes on an individual level for participants; (2) impact on social environments and neighbourhoods; and (3) the transnational collaboration. This paper presents selected results. Positive developments in the health-related behaviour of the training participants were recorded. Primary networks, such as family relationships, were shown to be supportive resources. It was not possible to determine any impact on the neighbourhoods. The transnational collaboration was perceived as enriching. At the same time, there were challenges in involving the health professionals in the evaluation process, such as restricted time for joint reflection and a lack of research skills in the community practitioners. In conclusion, the project was successful in developing a health-promoting approach that received a strong response in the German and Danish municipalities involved.